Kesadaran konstitusional gen z: membangun negara dengan nilai demokrasi - anggraeni, rahma permata (Maliki Interdisciplinary Journal, 2025)
Gen Z, who were born between the mid-1990s and early 2010s, play an important role in building the country through democratic values. With high digital skills and strong social awareness, Gen Z contributes to participatory processes, utilizing social media platforms to voice aspirations and advocate for issues of social justice, the environment and human rights. Gen z’s ways of getting involved in politics are creating social change and building an inclusive democratic culture. Thus, Gen Z is not only a successor, but also an important agent of change in strengthening democracy in their country. This abstract also aims to explore ways in which Generation Z can be involved in the process of understanding, forming, and implementing a more inclusive and progressive constitution. In addition, it is also explained how democratic values, such as active participation, social conditions, and respect for diversity, can be the main basis for national development. By relying on an approach based on civic education and the use of technology, it is hoped that Generation Z can become agents of change that encourage advanced countries to have a more robust and sustainable democratic system, with deeper constitutional awareness and responsibility.